RAPID DETECTION OF SARS COV-2 INFECTION IN COMPARISION WITH RT-PCR IN TERTIARY CARE HOSPITAL - LAXMI, RAJAMANICKAM VENKATA; A, RAMYA; DUNDIGALLA, MAMATHA REDDY; GOUTHAMI, SERISENI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The goal of the present study was to assess the SARS-CoV-2 antigen detection test’s performance features and compare them to the real-time reverse transcription polymerase chain reaction (RT-PCR) test, the gold standard test for the diagnosis of COVID-19 cases. Methods: From October 2020 to May 2021, patients attending the OPD, including those undergoing surgery, at a Tertiary Care Teaching Hospital in Telangana provided 1000 respiratory samples, primarily nasopharyngeal swabs. A skilled technician had collected two nasopharyngeal swabs from each person in a COVID sample collection room while wearing personal protective equipment and following strict infection control procedures. One swab was used for the rapid antigen test given by the standard Q COVID-19 Ag test kit and placed into the extraction buffer tube. Second swab was kept in the viral transport medium and used for Allplex™ 2019-nCoV Assay (Seegene, Korea), which targets envelope gene (E), and RNA dependent RNA polymerase (RdRp) and nucleocapsid (N) genes of SARS CoV-2, was used for SARS-CoV-2 RNA detection according to the manufacturer’s instructions. Results: Out of 1000 samples tested for COVID-19, 623 (63.7%) were males and 377 (36.3%) were females. Out of 1000 samples, 347 samples were RT-PCR positive and 653 were RT-PCR negative. Out of 347 RT-PCR samples positive, 341 were Rapid antigen test positive samples and six were negative. Overall sensitivity and specificity are 98.27% and 99.85%, respectively. Conclusion: The real-time RT-PCR assay’s sensitivity and specificity were comparable to those of the rapid assay for SARS-CoV-2 antigen detection. It can be utilized for contact tracing measures to control the COVID-19 pandemic in places such as border crossings, airports, interregional bus and train stations, and mass testing campaigns needing quick findings. This is especially true in areas with a high prevalence of the disease.